Critical action to redress systemic oppression: a person-centered approach - Vierra, Kristin; Barrita, Aldo; Wong-Padoongpatt, Gloria; Robnett, Rachael D. (Frontiers in Psychology, 2023)
In 2020, public outcry against police brutality prompted many social media users to post black squares and use the hashtag #BlackLivesMatter (BLM). Although the posts demonstrated support for BLM, many of the social media users failed to engage with BLM’s history or core principles and instead resorted to performative activism. The current study attempts to gain a deeper insight into the reasons why some individuals choose to participate in more impactful forms of activism while others opt for superficial or performative action to advocate for people who experience systemic oppression. To distinguish between more impactful compared to performative forms of activism, we employ critical action as our theoretical framework. Critical action is defined as individual or collective behaviors taken to create social change and challenge systems of oppression and is thereby a useful lens for distinguishing between different forms of activism. To provide nuanced, in-depth information about why people engage in different types of action, the current research leverages two methodological approaches: (1) A person-centered approach, which allowed us to identify subgroups in a sample of undergraduates who engaged in action to support BLM and (2) A mixed-methods approach, which allowed us to clarify and contextualize the quantitative subgroup analyses with qualitative analyses that focus on how participants reason about social action. A total of 359 undergraduates who reported that they engaged in some form of action to support BLM participated in this study. Latent profile analysis identified three subgroups (i.e., latent classes) in the larger sample, which we labeled (1) intentional action, (2) intermediate action, and (3) passive action. Participants in each latent class differed from one another in their sociopolitical attitudes, sociodemographic background, and level of action to support BLM. Through the qualitative coding process, the research team unearthed three overarching themes and a range of subthemes that that help to explain why the members of each class engaged in different forms of action. We conclude by proposing a flexible intervention that may motivate individuals to engage in critical action to support BLM. Keywords: Black Lives Matter, activism, critical action, performative action and systemic